The influence of structural imperfections on the LTB strength of I-beams. (February 2021) - Rossi, Alexandre; Hideyuki Saito, Daniel; Humberto Martins, Carlos; Sander Clemente de Souza, Alex
Highlights: The influence of residual stress patterns in the LTB strength was analyzed. Divergences in the LTB strength were verified according to the residual stress pattern adopted. Differences between experimental and numerical results were verified. The numerical analysis and standard procedures results presented divergences. Abstract: The structural imperfections, namely, the residual stresses, are generated during most manufacturing processes involving material deformation, heat treatment, machining or processing operations. The intensity and distribution of residual stresses are dependent on the techniques used in the production of steel sections (welding, rolling or cold formed techniques) and their dimensions. An appropriate evaluation of residual stress is of great importance for the structural performance of steel I-beams. Residual stresses can have a significant impact on the stability of structural members. In the case of I-section beam elements, such stresses can impact lateral torsional buckling (LTB) strength, particularly in the inelastic range. For the development of post buckling numerical analyses, the consideration of residual stress distribution models is fundamental for the correct determination of the LTB strength of I-beams. However, there are several models that attempt to represent the distribution and intensity of residual stresses. These models have a different influence on the LTB behavior of I-beams in numerical analysis. Therefore, this paper aims to investigate, through the development of post buckling numerical analyses with the ABAQUS software, the influence of the different residual stress distribution models on the LTB strength of I-beams. Seven different residual stress models were analyzed on simply supported I-beams subject to uniformly distributed loading applied in the shear center and in the upper flange. The results were compared with standard procedures. It was verified considerable divergences in LTB strength depending on the residual stress model applied. In addition, this paper presents a synthesis of the main residual stress distribution models. The analyses showed in this work shall help the choice of the residual stress distribution model on future numerical simulations.